PENGARUH MOTIVASI DAN LITERASI KEUANGAN TERHADAP MINAT BERINVESTASI PADA PASAR MODAL SYARIAH - Wan Gustina Indah Sari; Debbi Chyntia Ovami (Universitas Bina Bangsa, 2021)
The objective of this research was to test and analyze the influence of motivation and financial literacy on investment interest in Islamic capital markets with case studies of students of Universitas Muhammadiyah Sumatera Utara. This research used primary data, namely by spreading questionnaires through google form. Respondents in this research were undergraduate students majoring in accounting in 2018 and 2019. The number of samples in this research was 125 respondents. From the spread of the questionnaire, as many as 102 respondents (the number who filled out the questionnaire) that can be processed and analyzed with the help of the SPSS Computer Application Version 25 for windows. The statistical method used to test hypotheses was multiple linear regression analysis. The results showed that motivational variables and financial literacy variables simultaneously affect the variables of interest in investing in Islamic capital markets. This was evidenced by the Fobserved value of 116,999 and Ftable 3.09 with a significance of 0.000. The results also showed that motivational variables and financial literacy partially affected investing interests. This was evidenced by the value of tobserved > ttable where the value of tobserved motivation variable of 11,746 and the value of tobserved variable financial literacy of 3.533 while the value of ttable amounted to 1.660391.